Kebiasaan Makan dan Analisis Isi Lambung (Gut Content Analysis) Ikan Tangkapan di Talaga Jati Taruna, Jatinangor - Angellica, Angellica; Pribadi, Tri Dewi Kusumaningrum (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine the feeding habits and analyze the stomach contents of the fish caught in the waters of Talaga Jati Taruna. This study was conducted in an exploratory approach by obtaining fish samples from the fishers, followed by morphometric analysis and identification of natural food types in the digestive tract. The results showed that Nile tilapia (Oreochromis niloticus) had a positive allometric growth pattern with a regression coefficient (b) of 3.15 and a determination value of 0.99, indicating that body weight gain was faster than length gain. The relative gut length (RLG) analysis showed that both species are classified as herbivores, with RLG values greater than 3. Diet composition showed that phytoplankton dominated the stomach contents of both species, with the Cyanobacteriia dominating the Nile tilapia diet (IP% = 73.3%) and the Dinophyceae dominant in Mozambique tilapia (IP% = 70.56%). Abiotic parameters were still within optimal ranges to support aquatic life. These findings emphasize the importance of phytoplankton and zooplankton availability as natural food sources in supporting the growth and ecological balance of the Talaga Jati Taruna aquatic ecosystem.